2013
DOI: 10.1016/j.gaitpost.2013.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral balance training enhances neuromuscular reactions to perturbations in the trained and contralateral limb

Abstract: The aim of this study was to investigate the effect of unilateral balance training on the reactive recovery of balance for both trained and untrained limbs. Twenty-three subjects were randomly assigned to either a control group (CG) or a training group (TG). The latter performed six weeks of balance training for the right leg. The pre- and post-training measurements were based on single leg standing posture on a moveable force platform which moved 6 cm anteriorly. TG subjects were tested on the trained (TR) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 32 publications
2
54
0
Order By: Relevance
“…Prior to analysis, force and center of pressure data were low-pass filtered (50 Hz, zero-lag butterworth 4 th order). The average center of pressure speed and the variability of the center of pressure speed (calculated as the standard deviation of the center of pressure speed) were computed from the 30 s plantar pressure standing data 50 and were analyzed using custom scripts on MATLAB ® (R2016b, Mathworks Inc., Natick, MA USA).…”
Section: Methodsmentioning
confidence: 99%
“…Prior to analysis, force and center of pressure data were low-pass filtered (50 Hz, zero-lag butterworth 4 th order). The average center of pressure speed and the variability of the center of pressure speed (calculated as the standard deviation of the center of pressure speed) were computed from the 30 s plantar pressure standing data 50 and were analyzed using custom scripts on MATLAB ® (R2016b, Mathworks Inc., Natick, MA USA).…”
Section: Methodsmentioning
confidence: 99%
“…It is believed that motor coordination is a key factor for injury prevention, as the gains in intermuscular coordination for landing may potentially reduce the likelihood of lower limb injuries. Wobble boards are simple and low‐cost devices widely used to investigate and improve balance and postural control . Previous studies have shown that such devices can provide fast improvement in balance performance with a long‐term retention, ultimately reducing the risk of ankle sprains by up to 50% .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, conventional balance training (CBT) performed on unstable surfaces and convex devices has been validated to improve postural stability ( Granacher et al, 2006 ; Gruber et al, 2007a , b ; Taube et al, 2008 ; Freyler et al, 2014 ) and to elicit functional and neuromuscular adaptations beneficial for fall avoidance, such as augmented muscle strength ( Bruhn et al, 2006 ). This includes explosive force and rate of force development ( Gruber and Gollhofer, 2004 ; Taube et al, 2007 ) as well as modified muscle activity, such as increased activation or reduced co-contraction by means of improved muscle coordination, induced by neural adaptations within the central nervous system ( Granacher et al, 2009 ; Nagai et al, 2012 ; Oliveira et al, 2013 ; Behrens et al, 2015 ). These neuronal adaptations were specified by higher amplitudes and shorter latencies in the early reflex responses in the shank muscles, resulting in augmented ankle joint stiffness ( Granacher et al, 2006 ) and reduced fall frequency ( Madureira et al, 2007 ) in response to postural perturbations.…”
Section: Introductionmentioning
confidence: 99%